Evaluation of Change in Center of Pressure During Perturbation of Balance Including Blindfolding in Healthy Dogs - Hayley Hall; Richard B. Evans; Makayla Balogh; Wanda J. Gordon-Evans (Animals)
Physiotherapy aims to improve postural dysfunction, often using balance exercises. The effects of rehabilitation-based balance exercises on postural control in dogs remains understudied. This study aimed to assess the impact of specific balancing exercises and blindfolding on center of pressure parameters in healthy dogs. Thirteen healthy adult dogs participated in the study. Center of pressure parameters were measured using a pressure platform during quiet standing, external perturbation, head turn, and blindfolded trials. External perturbation significantly increased the area of the elliptical sway, cranio-caudal excursion, and right–left excursion. Head turning led to large effect sizes, but no significant differences compared to quiet standing. Blindfolding led to medium to large effect sizes, though no significant differences were observed. The study confirmed that external perturbation challenges postural stability, resulting in increased sway. Head turning induces sway but may require further training or different methodologies for reliable outcomes. Blindfolding increased sway but was not statistically different. These findings underscore the potential use of perturbation-based exercises in canine rehabilitation to improve balance, while also highlighting the need for further studies to standardize balance challenges and explore the effects in dogs with orthopedic or neurological conditions.